Design of a Synchronous Generator of Permanent Magnets of Radial Flux for a Pico-Hydropower Station - Flores, Estefanía (2021)
The design of a radial flux permanent magnet synchronous generator is presented, which can produce a maximum power of 2 KW at 600 rpm. Once the design was made and its main characteristics determined, the analysis was carried out in MATLAB to observe the behavior of the generator in its operating range. SolidWorks was also used for the elaboration of 3D modeling and finally in ANSYS for its electromagnetic analysis. The objective of this design is that the generator can be installed in a Pico-Hydropower station located in an Ambato–Huachi–Pelileo irrigation channel, in the Tungurahua province in Ecuador. This will allow users to get benefit from electrical energy in difficult access areas. At the same time, when used in the irrigation channel, it will be able to illuminate the channel and thus allow to provide maintenance at any time of the day.